Adaptive thermal tomography; Defektoskopiya; № 1 - Vavilov V. P. Vladimir Platonovich (1994, 1994)
A new algorithm of thermal tomography based on the adaptation of numerical solution of thermal control problems to experimental results for surface temperature is described. Experimental study was conducted with the help of computerized thermographical tomograph when determining natural and artificial defects in carbon plastic specimens. Algorithm proposed allowed processing only the first four layers of material using seven thermovision images. Further improvement of adaptive tomography should be attempted.